Possibility of improving disease prediction using mathematical models - Ilenko-Lobach, N. V.; Boychenko, O. M.; Ilenko, N. M.; Salomatina, S. O.; Nikolishyna, E. V.; Karnauh, M. M.; Voloshyna, A. V.; Zaitsev, A. V.; Карнаух, Марина Миколаївна (My University, 2024)
Throughout their existence, people have sought to know what tomorrow holds for them. It was especially important to learn about a full life, illness or death. Science is the essence of human knowledge, which is organized according to certain principles, a real connection of judgments, predictions and problems of reality and its individual spheres or aspects. Various indexes are used in modern periodontology. Index assessment allows you to succinctly and conveniently display the static state of periodontal tissues in quantitative terms. With their help, you can get an idea of the prevalence, degree of severity, the course of the inflammatory-destructive or dystrophic process, evaluate the effectiveness of the treatment and the quality of dispensary work in a specific patient or dispensary group. Among the indices, clinical ones are especially defined. They are the main group of indices that allows the clinician to assess the state of the periodontal tissues in a variety of ways. With their help, you can get a general idea of the nature of the course of the disease, plan the amount of medical interventions, evaluate the effectiveness of the treatment and dispensation. Various indexes are used in modern periodontology. Index assessment allows you to succinctly and conveniently display the static state of periodontal tissues in quantitative terms. With their help, you can get an idea of the prevalence, degree of severity, the course of the inflammatory-destructive or dystrophic process, evaluate the effectiveness of the treatment and the quality of dispensary work in a specific patient or dispensary group. Among the indices, clinical ones are especially defined. They are the main group of indices that allows the clinician to assess the state of the periodontal tissues in a variety of ways. With their help, you can get a general idea of the nature of the course of the disease, plan the amount of medical interventions, evaluate the effectiveness of the treatment and dispensation.
Keywords: Forecasting; mathematical modeling; periodontal disease